History of the Rami Alms Tradition in Preserving Local Culture in Kertayu Village, Sungai Keruh District, Musi Banyuasin District (1970-2022) - Riya, Aiwa; Hudaidah, Hudaidah (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
Kertayu Village, located in Sungai Keruh Sub-district, Musi Banyuasin Regency, is an area rich in cultural heritage and local traditions that have been passed down from generation to generation. One of the traditions that still takes place in this village is the Sedekah Bumi tradition. This tradition consists of sedekah lemang, a local specialty, as an expression of gratitude to God for the abundant harvest. This research is motivated by the rapid social, economic, and technological changes that can affect the sustainability of local traditions. Globalization and modernization can threaten the existence of traditions such as earth alms, so this research aims to find out the history of the earth alms tradition and its preservation in Kertayu Village, Sungai Keruh District, Musi Banyuasin Regency in 2015-2020. Meanwhile, the specific purpose of this research is to provide a deeper understanding of how the Earth Alms tradition in Kertayu Village is able to survive and adapt in facing the challenges of the times. This research uses historical research methods with four research steps, namely heuristics, source criticism, interpretation, and historiography. The research generally found that the implementation of Sedekah Bumi from 2015 to 2020 involving all levels of society showed strong collaboration and upheld values. Indigenous activists play a crucial role in the adaptation and preservation of noble values, while the community is actively involved in efforts to maintain the relevance and value of this tradition. The challenges of modernization are met with strenuous efforts to maintain the continuity of this tradition by passing on its values to the younger generation.